ANIMAL LABORATORY, INTERACTIVE AND COMPUTER BASED LEARNING, IN ENHANCING BASIC CONCEPTS IN PHYSIOLOGY: AN OUTLOOK OF 481 UNDERGRADUATE MEDICAL STUDENTS - Shore, Najla; Khawar, Shireen; Qutab, Miraa; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2013)
Background: Laboratory exercises are intended to illustrate concepts and add an active learning component to courses. Since 1980s, there has been a decline in animal laboratories in medical physiology courses. Other cost-effective non-animal alternatives are being sought. The present study was designed to find out the students' opinion regarding the animal versus computer lab and whether innovative teaching methodologies helped students achieve their goals. Methods: Opinions of 481 female medical students of 2nd and 3rd year MBBS were included in the study. A questionnaire based on animal/computer based experiments and new teaching methodologies in physiology was voluntarily filled in by the students. Results: Majority of students immensely benefited from both the animal lab and other teaching methodologies. Conclusion: Although computer based learning is considered effective in helping students acquire basic concepts, there is evidence that some students acquire a more thorough understanding of the material through more advanced and challenging experience of an animal laboratory. The fact that such labs as well various teaching methods offer distinct educational advantages should be taken into account when courses are designed. Keywords: Animal Lab, animation, Learning technique, Physiology learning, Teaching methods